Mathématiques
Zayn7
13

Bonjour 3x-5 = 4(x-2) - (x-7) 5+(4x-10) = -5 - 2x 3(x-1) - (4x+2) - ( 6x+3) - 4(3x-7) S.V.P Merci de votre aide

+1
(1) Réponses
cabiven12

3x - 5 = 4 (x - 2) - (x - 7) 3x - 5 = 4 * x + 4 * (- 2) - x + 7 3x - 5 = 4x - 8 - x + 7 3x - 4x + x = - 8 + 7 + 5 0x = 4 x = 4/0 x --> impossible 5 + (4x - 10) = - 5 - 2x 5 + 4x - 10 = - 5 - 2x 4x + 2x = - 5 - 5 + 10 6x = 0 x = 0/6 x = 0 3 (x - 1) - (4x + 2) = (6x + 3) - 4 (3x - 7) 3 * x + 3 * (- 1) - 4x - 2 = 6x + 3 - 4 * 3x - 4 * (- 7) 3x - 3 - 4x - 2 = 6x + 3 - 12x + 28 3x - 4x - 6x + 12x = 3 + 28 + 3 + 2 5x = 36 x = 36/5 x = 7,2

Ajouter une réponse